Hubungan Komitmen Pernikahan dengan Kepuasan Pernikahan pada Pasangan Suami-Istri di Bali - Sheilla Revinar Baraba (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Marriage is often pursued with the expectation of finding enduring happiness and fulfillment. However, the reality of marital life can deviate from these aspirations. This study investigates the crucial role of marital commitment in shaping marital satisfaction among couples in Bali. Employing survey techniques, data was collected through questionnaires, utilizing a scale likert to measure both commitment and satisfaction levels. The results highlight a significant positive correlation between marital commitment and marital satisfaction. Specifically, higher levels of commitment are associated with increased marital satisfaction, while lower levels of commitment correspond to diminished satisfaction. Pearson product moment parametric correlation analysis substantiates these findings, revealing a correlation coefficient of r = 0.848 and p = 0.000 (p < 0.05). This study underscores the importance of marital commitment in fostering marital satisfaction, offering valuable insights for couples and practitioners alike.